THE INFLUENCE OF CORPORATE IMAGE ON CONSUMER PURCHASE INTENTION WITH TRUST AS A MEDIATING VARIABLE IN THE NEW PRODUCT LAUNCHING (NPL) GENTLE GEN AT MAYORA INDAH TBK COMPANY - Ayu Roulina Natalida Simorangkir; E. Elia Ardyan; Metta Padmalia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Currently, the FMCG industry is experiencing increasing competition, which encourages businesses/companies to continuously seek innovation, particularly through the introduction of new products. However, many new products fail due to a lack of differentiation and a lack of initial consumer demand. Corporate image is a key factor in determining the success of a new product launch. This is important because a positive public image can influence public opinion and foster consumer trust. This study focuses on PT Mayora Indah Tbk, emphasizing the introduction of the Gentle Gen liquid detergent product launched in 2022 as a strategic business move to market for a new product. The purpose of this study is to determine how corporate image influences consumer purchasing intentions, with trust acting as a mediating variable. This study uses a quantitative methodology using an online questionnaire survey. The sample was selected using purposive sampling, with respondents meeting requirements such as being at least 18 years old, making purchasing decisions for household goods, and having a basic understanding of the Mayora brand or Gentle Gen products. Using SmartPLS 4.0 software, data collected from a minimum of 100 respondents will be analyzed using Partial Least Squares (PLS). It is predicted that the research findings will demonstrate a beneficial and substantial impact of corporate reputation on consumer purchase intentions, both directly and indirectly through the trust variable. It is expected that the trust variable will function as a mediating element that strengthens this relationship. From an academic perspective, this study will explain the function of trust as a mediator in new product introductions in FMCG companies in Indonesia. This study provides useful insights for Mayora's marketing plan to increase the market success of Gentle Gen from a realistic perspective.